EVALUATION AND ANTIOXIDANT TEST OF SAFFRON FACE MIST AS A SKIN MOISTURIZER - Al-Bari, Akhmad; Pratiwi, Shoffi Ajeng; Ni'am, Musfirotun (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Saffron (Crocus sativus L.) is a medicinal plant used as a spice in food, but recent times have shown that has a role in cosmetics. The saffron stigma has antioxidant activity and is useful in cosmetics. Antioxidants can protect the skin from various types of cell damage due to free radicals from ultraviolet light, motor vehicle fumes, chemicals in food, chemicals, and drugs. The antioxidant content of saffron stigma makes it an ingredient in cosmetics such as face mist. Face mist is a cosmetic skin freshener that refreshes facial skin, removes residual oil from the skin, kills some skin microorganisms, and helps close the pores. The aim of this study was to evaluate the antioxidant properties of the saffron face mist. The evaluation of saffron face mist includes an organoleptic test based on odor, color, and shape/texture, a pH test using a universal pH indicator paper, a specific gravity test using a pycnometer, and a moisture test using a skin moisture meter. The saffron stigma antioxidant test was performed using the DPPH assay. The results showed that the face mist had a rose aroma, golden yellow color, and moist form, the specific gravity ranged from 1.0637 to 1.0689 g/mL, the pH was 6, the moisture value of the facial skin after the application of the face mist to the face ranged from 47.77 ± 3.81 – 56.52 ± 0.72 % ...